2016
DOI: 10.1186/s12885-016-2177-5
|View full text |Cite
|
Sign up to set email alerts
|

Stage of breast cancer at diagnosis in New Zealand: impacts of socio-demographic factors, breast cancer screening and biology

Abstract: BackgroundExamination of factors associated with late stage diagnosis of breast cancer is useful to identify areas which are amenable to intervention. This study analyses trends in cancer stage at diagnosis and impact of socio-demographic, cancer biological and screening characteristics on cancer stage in a population-based series of women with invasive breast cancer in New Zealand.MethodsAll women diagnosed with invasive breast cancer between 2000 and 2013 were identified from two regional breast cancer regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 34 publications
5
45
1
3
Order By: Relevance
“…This is in contrast with a study in South Africa where McCormack et al reported that late stage tumours were more likely to be estrogen and progesterone receptor negative, but noted no association with HER2 status. 38 In New Zealand, researchers have reported poorly differentiated tumour grade (II and III) in women with late stage disease, 16 similar to findings in the United States, by Lipscomb et al who found advanced stage breast cancer to be positively related with poorly differentiated tumour grade and HER2 type tumours. 14 Our sample size for this analysis was, however, very limited, and thus, the influence of tumour characteristics on stage at diagnosis still needs to be fully explored in the SSA setting.…”
Section: Discussionsupporting
confidence: 62%
“…This is in contrast with a study in South Africa where McCormack et al reported that late stage tumours were more likely to be estrogen and progesterone receptor negative, but noted no association with HER2 status. 38 In New Zealand, researchers have reported poorly differentiated tumour grade (II and III) in women with late stage disease, 16 similar to findings in the United States, by Lipscomb et al who found advanced stage breast cancer to be positively related with poorly differentiated tumour grade and HER2 type tumours. 14 Our sample size for this analysis was, however, very limited, and thus, the influence of tumour characteristics on stage at diagnosis still needs to be fully explored in the SSA setting.…”
Section: Discussionsupporting
confidence: 62%
“…There is also variation in the definition of what is considered a rural population. This study is based on substantially more detailed clinical data available (including accurate staging, screening history and presence of biological markers) from two clinical breast cancer registers in the Waikato and Auckland regions [9]. Waikato District Health Board has a large rural community with 60% of patients living outside the main centre of Hamilton, while Auckland on the other hand is mainly an urban community.…”
Section: Introductionmentioning
confidence: 99%
“…This showed 3.9% of NZ European women had metastatic breast cancer at diagnosis compared with 7.6% of Māori women (adjusted OR 1.86 95% CI 1.39–2.49) (Seneviratne et al . in press).…”
Section: Stage and Characteristics At Diagnosismentioning
confidence: 99%